2020
DOI: 10.1101/2020.07.09.196246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling the molecular players at the cholinergic efferent synapse of the zebrafish lateral line

Abstract: AbstractThe lateral line (LL) is a sensory system that allows fish and amphibians to detect water currents. LL responsiveness to external stimuli is modulated by descending efferent neurons. LL efferent modulation aids the animal to distinguish between external and self-generated stimuli, maintaining sensitivity to relevant cues. One of the main components of the efferent system is cholinergic, the activation of which inhibits afferent activity. Since LL hair cells (HC) share s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 102 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…Using this approach, we found that in developing neuromast organs, without any external stimuli, the efferent terminals contacting hair cells were spontaneously active (examples, day3, To further examine the role of cholinergic efferents in hair cell spontaneous activity, we took a pharmacological approach. Cholinergic efferents share a molecular mechanism that is conserved among vertebrate hair cell systems (Glowatzki and Fuchs, 2000;Hiel et al, 2000;Parks et al, 2017;Carpaneto Freixas et al, 2021). Acetylcholine released from these efferents acts on α9 or α10 nicotinic acetylcholine receptors (nAChR), which allows calcium to enter near the hair cell presynapse.…”
Section: Two-color Imaging Reveals No Link Between Spontaneous Activities In Hair Cells and Efferentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, we found that in developing neuromast organs, without any external stimuli, the efferent terminals contacting hair cells were spontaneously active (examples, day3, To further examine the role of cholinergic efferents in hair cell spontaneous activity, we took a pharmacological approach. Cholinergic efferents share a molecular mechanism that is conserved among vertebrate hair cell systems (Glowatzki and Fuchs, 2000;Hiel et al, 2000;Parks et al, 2017;Carpaneto Freixas et al, 2021). Acetylcholine released from these efferents acts on α9 or α10 nicotinic acetylcholine receptors (nAChR), which allows calcium to enter near the hair cell presynapse.…”
Section: Two-color Imaging Reveals No Link Between Spontaneous Activities In Hair Cells and Efferentsmentioning
confidence: 99%
“…To determine if this cascade of events impacts hair cell spontaneous activity, we applied α-bungarotoxin (α-Btx) and apamin, compounds that block α9 nAChRs and SK channels respectively. Recent work has shown that these compounds are effective at disrupting efferent neurotransmission onto lateral-line hair cells (Carpaneto Freixas et al, 2021). Because cholinergic signaling is thought to impact the hair cell presynapse, for our analyses we used a membrane-localized indicator memGCaMP6s which we have used previously to specifically measure spontaneous presynaptic calcium activity (Hiutung et al, 2019).…”
Section: Two-color Imaging Reveals No Link Between Spontaneous Activities In Hair Cells and Efferentsmentioning
confidence: 99%